2020
DOI: 10.1007/s00167-020-06104-3
|View full text |Cite
|
Sign up to set email alerts
|

The negative impact of the COVID-19 lockdown on pain and physical function in patients with end-stage hip or knee osteoarthritis

Abstract: Purpose The purpose of this study was to evaluate pain, functional impairment, mental health, and daily activity in patients with end-stage hip and knee osteoarthritis (OA) during the COVID-19 lockdown. Methods The study included 63 patients, with hip or knee OA, who had been scheduled for arthroplasty that was postponed because of COVID-19. Patients were evaluated by telephone interviews during the first week after lockdown, in the fourth week, and again at the end of the lockdown. Patients rated their pain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 25 publications
6
67
1
6
Order By: Relevance
“…Similarly, Endstrasser et al observed a time dependent decrease in SF-12 physical component scores as the COVID-19 pandemic progressed. 8 Similarly, our patients reported lower mHHS scores than would be expected in a pre-operative cohort. 16 …”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Similarly, Endstrasser et al observed a time dependent decrease in SF-12 physical component scores as the COVID-19 pandemic progressed. 8 Similarly, our patients reported lower mHHS scores than would be expected in a pre-operative cohort. 16 …”
Section: Discussionsupporting
confidence: 62%
“…In comparison, our cohort of patients had a mean PCS-12 score of 30.9 (SD ± 7.4), which is lower than a similar study conducted on an Austrian cohort. 8 Similarly, the mean MCS-12 score in our patients was 49.95 (SD ± 13.07), with the national average in patients >50 being 53.0 (SD ± 8.30). 17 …”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations